Macroeconomic Developments and Selected Issues in Small Developing States. (Policy Papers; Policy Paper, 2015)
This report builds on the work in the 2013 Board paper on Fund Engagement with Small States, the 2013 background papers on Asian and Pacific small states and Caribbean small states, and the 2014 staff guidance note. It provides a deeper analysis and policy recommendations in respect of three challenges identified in these papers. Looking ahead, the paper also analyses the impact and possible policy responses to two global economic trends-lower oil prices and diverse movements in major currencies.